Dynamic simulation and multi-objective optimization of a solar-assisted desiccant cooling system integrated with ground source renewable energy. (5th June 2020) - Rayegan, Saeed; Motaghian, Shahrooz; Heidarinejad, Ghassem; Pasdarshahri, Hadi; Ahmadi, Pouria; Rosen, Marc A.
Highlights: Dynamic simulation-multi objective optimization of the SDCS-GSHE is performed. The potential of SDCS-GSHE is studied for extremely hot and humid conditions. Different optimization approaches are applied to design proposed cooling system. High level of thermal comfort are achieved with averaged SF equal to unity. High performance DW requires lower energy to provide thermal comfort level. Abstract: This study presents a dynamic simulation-optimization of a solar-assisted desiccant cooling system integrated with a ground source heat exchanger (SDCS-GSHE). Solar and ground source energies are used for regenerating the desiccant wheel (DW) and a pre-cooling process, respectively. The system is considered as an alternative for extremely hot and humid regions. Determinant design parameters of the SDCS-GSHE that are associated with the DW, GSHE, and solar loop components directly affect the system behavior and, consequently, the provided thermal comfort, as well as the solar fraction (SF). Therefore, a multi-objective genetic algorithm optimization is invoked to determine all viable optimum design parameters to set up the system. Also, an economic assessment of the system is performed to demonstrate its economic feasibility. With the results, the optimum regeneration temperature, number of ground boreholes, collector area can be determined based on the required level of thermal comfort and the SF. The results reveal that, in the absence of the GSHE, the system cannot provide thermal comfort in extremely humid regions even with high regeneration temperatures (around 120 °C). Instead, using the GSHE dramatically improves the established thermal comfort. For regeneration temperatures below 90 °C, it is determined that the total necessary energy can be supplied entirely by solar energy. For the best case, in which the system successfully provides thermal comfort, the cost payback period for the system is found to be 5.7 years.